Paradoks Keaktifan Klasial Studi Komparatif Model Pembelajaran Lintas Situs Dan Fenomena Focus Gap Pada Anak Usia Dini - Maria Yunita Dhema; Putu Arya Oka; Patrisia Serlinda Meo; Maria Edo Meo; Maria Rosamistika Ina Soa; Tekla Dua Ona; Grasiana Sandra Mugi; Edeltrudias Bena; Katarina Ndekung; Maria Wilhelmina Mamo; Maria Fancelina Sugi; Florentina Wonga Rua; Maria Nadila Wea (Jurnal Inovasi Pendidikan Dan Pembelajaran, 2026)
behavioral indikator defferences between Class A (passive-dependent) and Class B (extrovert-participatory), while identifying the underlying causes of the "Focus Gap" phenomenon. Data analisis followed the Miles and Huberman model, comprising data condensation, data display, and conclusion drawing/verification, which was subsequently validated through spatial triangulation. The findings reveal that Class A consistently exhibits a well-ordered, teacher-centered pattern characterized by a minimal level of verbal initiative. Conversely, Class B which utilizes an interactive-ezperimental learning model successfully triggers a surge in intrinsic motivation and a This qualitative study employs a multi-site design across three preschools TKK Negeri St. Gabriel Ngabheo, TK Nazareth Were, and TKK Negeri Cinta Damai aiming to map the prosocial character of mutual cooperation (gotong royong). However, Class B encounters a paradox in the form of a "Focus Gap". Verbal engagement in Class B is heavily dominated by Peer-imitation patterns. Only a small fraction of the children manage to maintain an adequate attention span toward visual media, whereas the remainder experience rapid focus degradation driven by the internet egocentrism of the pre-operational developmental stage. This study recommends individual scaffolding strategis to address the passivity in Class A, alongside the rigorous implementation of instructional pacing and listening skill stimulation to effectively regulate children's cognitive attention in Class B.